2006
DOI: 10.1007/s10592-006-9150-9
|View full text |Cite
|
Sign up to set email alerts
|

Conservation genetics in hypersaline inland waters: mitochondrial diversity and phylogeography of an endangered Iberian beetle (Coleoptera: Hydraenidae)

Abstract: Saline inland waters are globally threatened habitats harbouring many specialised endemic species, which often have restricted geographic ranges, and occur as highly isolated populations. We studied the genetic variation and phylogeography of Ochthebius glaber Montes and Soler, a rare and endangered water beetle endemic to hypersaline streams in the South and Southeast of the Iberian Peninsula. We used a 633 bp fragment of cytochrome oxidase subunit 1 gene to determine the genetic diversity and phylogeographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 53 publications
2
62
0
2
Order By: Relevance
“…Even though more studies must be carried out to support the findings of this work, our results showed that rice fields, endorheic lagoons and continental saltpans have specific water beetles assemblages which could be used as a key factor for bioassessment and conservation studies (Menetrey et al 2005;Oertli et al 2005). Continental salt-pans constituted a homogeneous group due to the high salt content of water, with conductivity values of about 200,000 lS/ cm in many cases (Abellán et al 2007;Gutiérrez-Cánovas et al 2008). Under these environmental constraints, only four species were able to survive, Ochthebius notabilis being the best indicator species inhabiting this kind of habitat.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Even though more studies must be carried out to support the findings of this work, our results showed that rice fields, endorheic lagoons and continental saltpans have specific water beetles assemblages which could be used as a key factor for bioassessment and conservation studies (Menetrey et al 2005;Oertli et al 2005). Continental salt-pans constituted a homogeneous group due to the high salt content of water, with conductivity values of about 200,000 lS/ cm in many cases (Abellán et al 2007;Gutiérrez-Cánovas et al 2008). Under these environmental constraints, only four species were able to survive, Ochthebius notabilis being the best indicator species inhabiting this kind of habitat.…”
Section: Discussionsupporting
confidence: 58%
“…In addition, although there are very few narrow range endemic species of water beetle found in standing waters (Ribera et al 2003), four endemics were collected in our study, one of them being exclusive to lentic ecosystems. These species were found in mineralized water bodies where it is more usual to find rare or endemic invertebrate species Abellán et al 2007). A good example of this is the presence of Ochthebius irenae, the only known endemic species from standing saline waters in the Iberian Peninsula (Ribera and Millán 1999;Abellán et al 2005), a taxon which is also highly threatened (Sánchez- Fernández et al 2008a).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that lentic invertebrates exhibit on average lower genetic population differentiation than lotic species, in a consistent way across the three studied groups. Abellán et al (2007) reported high levels of genetic divergence among populations of Ochthebius glaber, a species of Coleoptera exclusive to hypersaline running waters in south-east Spain. Although the comparative data were preliminary, nucleotide diversity within O. glaber was an order of magnitude higher (0.026 and 0.004, respectively) than a closely related species, O. notabilis, which is exclusive to hypersaline standing waters, despite the larger area occupied by populations of O. notabilis (from the Pyrenees to the south of the Iberian Peninsula).…”
Section: Genetic Fl Ow Among Populationsmentioning
confidence: 99%
“…Although some authors (e.g., Crandall et al 2000) have recently called for incorporation of ecological and/or genetic data of adaptive significance into the formulation of ESUs, the collection of these kinds of data was beyond the original aims of this study. Nonetheless, the significant geographical structuring of genetic variation found in the Tehuantepec jackrabbit may have promoted as yet undetected local adaptation that may be important in maintaining the adaptive potential of the species (Abellán et al 2007). Conservation actions should include all populations of L. flavigularis, but the restricted distribution of jackrabbits from Santa María del Mar indicates that this population is particularly and highly vulnerable to extinction.…”
Section: Conservation Implicationsmentioning
confidence: 99%